Emerging roles of long noncoding RNA H19 in human lung cancer - Ahmad, Irfan; Jasim, Saade Abdalkareem; Sergeevna, Klunko Nataliya; Jyothi.S, Renuka; Kumar, Ashwani; Dusanov, Abdigafur; Shuhata Alubiady, Mahmood Hasen; Sinha, Aashna; Zain Al‐Abdeen, Salah Hassan; Hjazi, Ahmed (Cell biochemistry and function, 2024)
Lung cancer holds the position of being the primary cause of cancer‐related fatalities on a global scale. Furthermore, it exhibits the highest mortality rate among all types of cancer. The survival rate within a span of 5 years is less than 20%, primarily due to the fact that the disease is often diagnosed at an advanced stage, resulting in less effective treatment options compared to earlier stages. There are two main types of primary lung cancer: nonsmall‐cell lung cancer, which accounts for approximately 80%–85% of all cases, and small‐cell lung cancer, which is categorized based on the specific type of cells in which the cancer originates. The understanding of the biology of this disease and the identification of oncogenic driver alterations have significantly transformed the landscape of therapeutic approaches. Long noncoding RNAs (lncRNAs) play a crucial role in regulating various physiological and pathological processes through diverse molecular mechanisms. Among these lncRNAs, lncRNA H19, initially identified as an oncofetal transcript, has garnered significant attention due to its elevated expression in numerous tumors. Extensive research has confirmed its involvement in tumorigenesis and malignant progression by promoting cell growth, invasion, migration, epithelial‐mesenchymal transition, metastasis, and therapy resistance. This comprehensive review aims to provide an overview of the aberrant overexpression of lncRNA H19 and the molecular pathways through which it contributes to the advancement of lung cancer. The findings of this review highlight the potential for further investigation into the diagnosis and treatment of this disease, offering promising avenues for future research. Significance Statement Since today the role of different long noncoding RNAs (lncRNAs) in the development of various cancers has been determined to some extent, our aim is to investigate the role of lncRNA H19 in the progression of lung cancer. It is hoped that with a comprehensive review of past studies, this lncRNA can be used as a target for identifying and treating this cancer.